Experimental Study on the Mechanical Properties of Glass Fiber Reinforced Epoxy at Elevated Temperature - Chow, Z. P.; Ahmad, Z.; Wong, K. J. (International Journal of Automotive and Mechanical Engineering, 2019)
This paper presents the effects of elevated temperature on the mechanical response of a glass fibre reinforced epoxy (GFRE) composite. The mechanical properties taken into account are tensile, compression and shear. All tests are carried out at temperatures of 30°C, 70°C and 110°C, below the glass transition temperature of the resin. The properties along fibre direction and perpendicular to fibre direction are investigated, with two sets consisting of 0° and 90° fibre direction for tensile and compression tests. Stress-strain profiles at each temperature are firstly compared. Subsequently, the elastic modulus and the ultimate strength with respect to temperature are assessed. The results indicate that tensile properties remain relatively unaffected at 70°C but drop rapidly at 110°C. In addition, compressive properties decrease steadily from 30°C to 110°C, while shear properties are heavily degraded with increasing temperature. Fibre dominated properties have better heat resistance compared to matrix dominated properties due to matrix softening and weakening.